Policy rule evaluation by contract-markets: 100 years of wage contract lenght in Sweden - Fregert, Klas.; Jonung, Lars.; European Commission : Directorate-General for Economic and Financial Affairs (Bruxelles- Luxembourg: European Comission: Directorate-General for Economic and Financial Affairs, 2006)
The length of collective wage agreements in Sweden between 1908 and 2005 is explored to evaluate a variety of policy regimes from the wage contract-makers' perspective. Adopting a new long-run test, it is found that wage contract length decreases in response to an increase in "macroeconomic uncertainty" across policy regimes. There is also substantial short-run variation in contract length, which cautions against regime divisions based solely on the policy rule. The inflation targeting regime 1995-2005 stands out as an exceptionally stable policy regime as judged by the willingness of contract-makers to repeatedly commit to three-year non-indexed wage agreements. The results are based on a data base on collective wage agreements unique in international comparisons in terms of length and coverage.
Economic Papers